Implementing a resident wellness program for Psychiatry residents - Generoso, Marcelo Bruno (2024)
Medical residency is a challenging period that can negatively impact the mental health of resident doctors. Studies point to high rates of burnout, depression and anxiety disorders in this population. The Psychiatry Network-Based Medical Residency Program of the Municipal Health Department of São Paulo developed a pioneering Resident Wellness Program focused on promoting well-being and preventing mental illness. The program offers five fronts: establishing an environment of open dialogue about well-being in medical residency, supervised peer support groups, seminars and training to preserve well-being, encouraging the practice of physical activity and reception and referral for treatment when necessary. We chose to include seminars, training and groups in the program’s regular timetable for better acceptance of the strategies. The program is recent and has an innovative model in Brazil with a focus on promoting health and well-being. Given the urgency of the topic, we encourage program supervisors and coordinators of Medical Residency Committees in Brazil to seek to develop similar programs.